Signal combination in flutter vibration perception - Shasha Wei; Alex R. Wade; Catherine E.J. Preston; Daniel H. Baker (PLoS ONE, 2026)
While the brain’s integration of auditory and visual inputs has been extensively investigated, the mechanisms underlying somatosensory signal combination remain less explored. Here, we combine psychophysical thresholds with steady-state somatosensory evoked potentials (SSSEPs) to investigate how vibrotactile inputs are combined across fingers. We find that doubling the number of stimulated digits leads to a weak improvement in detection threshold, consistent with probability summation, whereas introducing a masking stimulus to interleaved digits induces inter-digit suppression. Correspondingly, EEG recordings reveal a ~ 1.4-fold increase in SSSEP amplitude when doubling the number of digits stimulated at the same frequency, reflecting a summation effect. In contrast, SSSEP amplitudes decrease when digits are vibrated at two different frequencies, further supporting the presence of suppression. These results are consistent with a model featuring inhibition between digits and reveal that the weight of suppression is intermediate between that observed in binocular vision and binaural hearing.